دور العلاقات العامة في وضع استراتيجية تضمن للجمعيات الخيرية الاستمرار في نشاطها - جمعية إيثار لرعاية الأيتام أنموذجا- - عريق, لطيفة; هويدي, عبد الباسط (جامعة الوادي - University of Eloued, 2021)
تهدف هذه الدراسة من أجل إيجاد استراتيجية خاصة بإدارة الجمعيات الخيرية حتى تضمن لها الاستمرار في نشاطها، فتم التطرق إلى مفهوم العلاقات العامة، وأهميتها وأهدافها، وكذا مفهوم كل من الإستراتيجية والتخطيط الاستراتيجي، وأخيرا وضع استراتيجية خاصة بإدارة الجمعيات الخيرية. وقد توصلت الدراسة إلى أن التخطيط الاستراتيجي لجمعية إيثار هو نفسه التخطيط الاستراتيجي الذي تقوم عليه إدارة العلاقات العامة الذي يتركز على أتباع الأسلوب العلمي والإعلام الصادق من أجل تحقيق الجمعية أهدافها وتوسيع نشاطها والحفاظ على أعضائها وكسب أعضاء جدد وللحصول على المال الكافي للاستمرار في نشاطها ومساعدة الفئات المعنية بالخدمات.This study aims to find a certain strategy for the management of charity associations in order to ensure the continuation of charity associations activities, we dealt with the concept of public relations, their importance and goals, as well as the concept of the strategy and strategic planning, and eventually coming up with a strategy for the management of charity associations. The study found that the strategic planning of ITHAR association is the same strategic planning carried out by the public relations management, which is based on scientific method and the objective media in order for the association to achieve its objectives and expand its activities and in order to preserve its members, gain new members and get enough money to continue its activities for the benefit of the concerned categories.
The role of public relations in the development of a strategy that ensures the continuation of charity associations activities. - ITHAR association for Orphans as a model -
مقال
Keywords: العلاقات العامة، الإستراتيجية، التخطيط، التخطيط الاستراتيجي، الجمعيات الخيرية.; public relations, strategic, strategic planning, charity associations.